Kajian Tindak Tutur Dalam Film Bilal: A New Breed of Hero - Vera Nurfitriani (Alfaz (Arabic Literatures for Academic Zealots), 2022)
Bilal: a new breed of hero is a 3d computer animation film produced Arabic using English directed by ayman jamal and khurram h. alavi in 2015 and released in 2016. Although the film is English in general, it is also produced in Arabic. The study focuses on illocution and perlocution speech act by using Austin and searle's speech of acts theories in order to find out what a speaker and his type's speech represents in the Arabic version of bilal: a new breed of hero. The method used in this study is a qualitative descriptive method. The results of the study reveal that there are four types of illocution speech acts which are aserctive, directive, commissive and expressive. For perlocutions speech act is found in two types, there are non-verbal perlocution and verbal non-verbal perlocution